SUSTAINED-HIGH ECONOMIC GROWTH AND CHANGES IN FORMAL INSTITUTIONS IN INDONESIA - Ramlan Surbakti, Drs., MA, PhD. (LEMBAGA PENELITIAN UNIVERSITAS AIRLANGGA, 1996)
The objective of this research is to discuss a classic but remain interesting topics regarding the relationship between sustained-high economic growth and the governmental structure and process (formal institutions) during the New Order government of Indonesia. The relation between the two variables, at least in Indonesia, has two ways of direction. One puts economic growth as an independent variable, and the other puts governmental structure and process as an independent variable.